Low-haze scratch-resistant polypropylene composite material as well as preparation method and application thereof

By adding acrylamide and POSS to the polypropylene system, the problem of degradation of scratch resistance at high temperatures is solved, the material is low haze and high light transmittance, and the preparation cost is reduced.

CN119859371AActive Publication Date: 2025-04-22NINGBO HAIYUE NEW MATERIAL +1

Patent Information

Application Number
CN202411970283.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-22
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing polypropylene materials have reduced scratch resistance at high temperatures, and the added scratch resistance will affect the light transmittance of the material and increase the preparation cost.

Method used

By adding acrylamide and POSS to the polypropylene system, the migration speed and compatibility of amide-based scratch-resistant agents can be improved, so that they can quickly migrate to the surface during the polypropylene crystallization process, forming scratch-resistant films, and improving the light transmittance and tensile strength of the material through the cage network structure of POSS.

Benefits of technology

The excellent scratch resistance of polypropylene composite materials at room temperature and high temperature is achieved, which reduces the haze of the material, improves the light transmission performance, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219351150000051
    Figure BDA0005219351150000051
  • Figure BDA0005219351150000062
    Figure BDA0005219351150000062
  • Figure BDA0005219351150000063
    Figure BDA0005219351150000063
Patent Text Reader

Abstract

The invention provides a low-haze scratch-resistant polypropylene composite material. The low-haze scratch-resistant polypropylene composite material is prepared from the following components in parts by weight: 100 parts of polypropylene, 0 to 55 parts of filler, 5 to 30 parts of acrylamide, 10 to 55 parts of POSS (Polyhedral Oligomeric Silsesquioxane), 0.01 to 0.1 part of amide scratch-resistant agent and 0 to 1 part of other auxiliaries. Acrylamide and POSS are added into the polypropylene composite material to synergistically improve the thermal scratch resistance of the material at normal temperature and high temperature and reduce the influence of an amide scratch-resistant agent on the haze of the polypropylene material, so that the prepared polypropylene composite material has excellent normal-temperature and high-temperature aging and scratch resistance and low haze.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of engineering plastics, and more specifically to a low-haze scratch-resistant polypropylene composite material and a preparation method and application thereof. Background Art

[0002] Polypropylene is widely used in automobiles due to its low density, high cost performance, excellent heat resistance, rigidity, chemical resistance, easy processing and recycling, and has become the largest and fastest growing variety of automotive plastics. In recent years, the rapid development of the automotive industry has put forward higher and higher requirements for interior and exterior materials, such as high strength, impact resistance, scratch resistance, and good dimensional stability for instrument panels, door panels, and bumpers.

[0003] Since the surface of polypropylene materials is easily scratched by external forces, it will greatly affect the appearance of the products, limiting its wide application in automotive interior products. At present, most of the scratch resistance of polypropylene materials is improved by adding scratch resistant agents. However, the scratch resistant agents currently added are mainly amide scratch resistant agents and silicone scratch resistant agents. Amide scratch resistant agents will affect the light transmission performance of polypropylene materials, especially increase the haze, affecting the appearance. In addition, amide scratch resistant agents will degrade and precipitate under the action of light and heat, causing the scratch resistance of the material to decrease, and cannot meet the application requirements of automotive interiors in high temperatures outdoors in summer. Although silicone scratch resistant agents have little effect on the light transmission performance of polypropylene, due to their large molecular weight, their activity in the matrix is ​​not as good as amide scratch resistant agents. Therefore, the scratch resistance effect is poor, and compared with amide scratch resistant agents, they need to be added in large quantities, which increases the preparation cost.

[0004] Chinese patent CN117126493A discloses a highly scratch-resistant and light-transmitting polypropylene material. The invention adopts a specially designed hardening and light-transmitting agent, which is a copolymer of POSS (methacryloxypropyl cage-type polysilsesquioxane), nadic anhydride, glycidyl methacrylate and / or maleic anhydride. At the same time, a high-transparency random copolymer polypropylene and a homopolymer polypropylene with a high surface hardness are selected for compounding, and a high-transparency elastic material is matched. A light diffuser is used to achieve uniform distribution of light and a nucleating agent is used to reduce the crystal size, thereby improving the light transmittance and scratch resistance of the material. However, the hardening and light-transmitting agent and the scratch-resistant agent have limited effects on improving the scratch resistance of the surface of the polypropylene composite material, and excessive addition of the scratch-resistant agent will affect the light transmittance of the material.

[0005] Therefore, how to provide a polypropylene composite material having both excellent scratch resistance at room temperature and high temperature and low haze is still a technical problem that needs to be solved urgently. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the above-mentioned problems in the prior art and provide a low-haze, scratch-resistant polypropylene composite material.

[0007] The second object of the present invention is to provide a method for preparing a low-haze scratch-resistant polypropylene composite material.

[0008] The third object of the present invention is to provide the use of the low-haze scratch-resistant polypropylene composite material in the preparation of automotive parts.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A low-fog, scratch-resistant polypropylene composite material comprises the following components in parts by weight:

[0011] 100 parts of polypropylene, 0-55 parts of filler, 5-30 parts of acrylamide, 10-55 parts of POSS, 0.01-0.1 parts of amide anti-scratch agent, and 0-1 parts of other additives.

[0012] The propylene group in the acrylamide added by the present invention can ensure that it has certain compatibility and diffusion capacity in the polypropylene matrix; acrylamide and POSS act together, and the migration speed of amide scratch-resistant agent in the polypropylene matrix can be further improved, so that in the polypropylene crystallization process, more scratch-resistant agent can quickly migrate to the surface of the polypropylene material, and a scratch-resistant film is formed on the surface, so that the scratch resistance of polypropylene composite material at room temperature and high temperature is significantly improved; meanwhile, the amide bond in acrylamide has polarity, and has a certain adsorption effect with the silicon oxygen bond in POSS, and POSS can be formed into a stable agglomerate of smaller particle size in the polypropylene matrix, so that the crystalline phase of polypropylene is evenly distributed, and a certain network structure is formed, thereby preventing the small molecules produced by amide scratch-resistant agent from precipitating out of the material surface, affecting the haze of polypropylene material, and further improving the light transmission performance of material. In addition, described POSS has a cage network structure, which can provide a supporting effect in the system, so that the tensile strength of polypropylene composite material is improved.

[0013] Preferably, the melt flow rate of the polypropylene at 230° C. and 2.16 kg is 1 to 60 g / 10 min.

[0014] In the present invention, the melt flow rate of the polypropylene can be 1 g / 10min, 5 g / 10min, 10 g / 10min, 15 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 35 g / 10min, 40 g / 10min, 45 g / 10min, 50 g / 10min, 55 g / 10min, 60 g / 10min, etc., or any value within the range.

[0015] More preferably, the melt flow rate of the polypropylene at 230°C and 2.16kg is more preferably 10 to 35 g / 10min. That is, the melt flow rate of the polypropylene can be 10 g / 10min, 12 g / 10min, 14 g / 10min, 16 g / 10min, 18 g / 10min, 20 g / 10min, 22 g / 10min, 24 g / 10min, 26 g / 10min, 28 g / 10min, 30 g / 10min, 32 g / 10min, 35 g / 10min, etc., or an interval range formed by any of the above values, such as 10 to 20 g / 10min, 25 to 35 g / 10min, etc., but is not limited thereto.

[0016] When the melt flow rate of the polypropylene is within this range, the polypropylene composite material system has good fluidity, which is conducive to uniform mixing of the raw material components. Polypropylene with both high light transmittance and scratch resistance can be prepared. The melt flow rate (MFR) of the polypropylene is measured according to the standard method of "ISO 1133-1:2011".

[0017] Preferably, in the low-haze and scratch-resistant polypropylene composite material, the mass content of polypropylene is not less than 42%.

[0018] Preferably, the polypropylene includes at least one of block copolymer polypropylene, homopolymer polypropylene and random copolymer polypropylene.

[0019] More preferably, the polypropylene is block copolymer polypropylene.

[0020] Preferably, the filler includes at least one of talc, calcium carbonate, and basic magnesium sulfate whiskers.

[0021] Preferably, the POSS comprises at least one of octaaminopropyl cage-type polysilsesquioxane and its derivatives, octa-glycidyl cage-type polysilsesquioxane and its derivatives, octacarboxyethylene cage-type polysilsesquioxane and its derivatives, and octamethacryloxypropyl cage-type polysilsesquioxane and its derivatives.

[0022] Preferably, the amide anti-scratch agent includes at least one of erucamide and oleamide.

[0023] Preferably, the other auxiliary agent is an antioxidant.

[0024] Preferably, the antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant.

[0025] The amount of the hindered phenol antioxidant added is preferably 0.1 to 0.3 parts.

[0026] The amount of the phosphite antioxidant added is preferably 0.1 to 0.3 parts. More preferably, the hindered phenol antioxidant is antioxidant 1010; and the phosphite antioxidant is antioxidant 168.

[0027] The method for preparing the low-haze scratch-resistant polypropylene composite material comprises the following steps:

[0028] According to the above weight parts, polypropylene, filler, acrylamide, POSS, amide scratch-resistant agent and antioxidant are uniformly mixed and melt-extruded to prepare the low-haze scratch-resistant polypropylene composite material.

[0029] Preferably, the temperature of the melt extrusion is 170-210°C.

[0030] Preferably, the melt extrusion is carried out using a twin-screw extruder, and the temperatures from the feeding section to the die head of the twin-screw extruder are 170±5℃, 200±5℃, 200±5℃, 210±5℃, 210±5℃, 205±5℃, 205±5℃, 205±5℃, 200±5℃, and 200±5℃ respectively.

[0031] Application of the low-haze scratch-resistant polypropylene composite material in the preparation of automotive parts.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention adds acrylamide and POSS to a polypropylene system using amide substances as scratch resistant agents, thereby overcoming the influence of amide scratch resistant agents on the haze of polypropylene materials and the influence of amide scratch resistant agents that are easily decomposed at high temperatures on the scratch resistance of the material, so that the prepared polypropylene composite material has both excellent scratch resistance at room temperature and high temperature and low haze, and surprisingly, the tensile performance is further improved.

[0034] In addition, the polypropylene composite material of the present invention has a simple preparation formula and process, can reduce production costs, and has practical application value. DETAILED DESCRIPTION

[0035] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0036] The embodiments of the present invention adopt the following raw materials:

[0037] Polypropylene:

[0038] Polypropylene 1: BX3500 (block copolymer polypropylene, MFR = 10 g / 10 min at 230°C and 2.16 kg load), purchased from Aiskai, Korea;

[0039] Polypropylene 2: BX3800 (block copolymer polypropylene, MFR = 30 g / 10 min at 230°C and 2.16 kg load), purchased from Aiskai, Korea;

[0040] Polypropylene 3: SZ30S (homopolymer polypropylene, MFR = 30 g / 10 min at 230°C and 2.16 kg load), purchased from Sino-Korean Petrochemical (Wuhan);

[0041] Polypropylene 4: SM198 (random copolymer polypropylene), MFR = 2.5 g / 10 min at 230°C and 2.16 kg load, purchased from Malay Datang;

[0042] Polypropylene 5: BX3900 (random copolymer polypropylene, MFR = 60 g / 10 min at 230°C and 2.16 kg load), purchased from Aiskai, Korea;

[0043] filler:

[0044] Calcium carbonate: 75T, purchased from Changxing Omiya;

[0045] Whiskers: WS-1S2 (basic magnesium sulfate whiskers), purchased from Yingkou Kangru Technology;

[0046] Talc: TYT-777A (3000 mesh talc), purchased from Liaoning Tianyuan;

[0047] Scratch resistant agent:

[0048] Erucic acid amide: purchased from Shanghai Kaiyin Chemical;

[0049] Oleic acid amide: purchased from Shanghai Kaiyin Chemical;

[0050] Silicone masterbatch: MB25-502, purchased from Dow Corning, USA;

[0051] Acrylamide: Commercially available;

[0052] POSS:

[0053] Octamethacryloxypropyl cage-type polysilsesquioxane (MMA-□POSS): purchased from HybridPlastics, USA;

[0054] Octaaminopropyl cage-type polysilsesquioxane: purchased from Hybrid Plastics, USA;

[0055] Antioxidants:

[0056] Antioxidant 1010: commercially available;

[0057] Antioxidant 168: commercially available.

[0058] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.

[0059] Example 1

[0060] A low-haze, scratch-resistant polypropylene composite material, the weight proportions of the raw materials used are shown in Table 1.

[0061] The method for preparing the low-haze scratch-resistant polypropylene composite material comprises the following steps:

[0062] According to the weight parts in Table 1, polypropylene, filler, acrylamide, POSS, amide scratch-resistant agent and antioxidant are uniformly mixed and melt-extruded to prepare the low-haze scratch-resistant polypropylene composite material. The melt extrusion is carried out using a twin-screw extruder, and the temperatures from the feeding section to the die of the twin-screw extruder are 170°C, 200°C, 200°C, 210°C, 210°C, 205°C, 205°C, 205°C, 200°C, and 200°C, respectively.

[0063] Example 2 to Example 14 and Comparative Example 1 to Comparative Example 4

[0064] The weight parts of the raw materials used in Examples 2 to 14 and Comparative Examples 1 to 4 are shown in Table 1. The preparation steps of Examples 2 to 14 and Comparative Examples 1 to 4 are the same as that of Example 1.

[0065] Table 1 Formula components of Example 1 to Example 14

[0066]

[0067]

[0068] Table 1

[0069]

[0070] Table 2 Formula components of Comparative Examples 1 to 4

[0071]

[0072] Performance Testing

[0073] The properties of the polypropylene composite materials obtained in the above examples and comparative examples were characterized, and the specific test items, test methods and results are as follows:

[0074] (1) The scratch resistance test was carried out according to PV3952, with a load of 10N. The scratch resistance of the sample was evaluated by measuring the ΔL value (i.e., the change mark of black and white color) on the surface of the scratched sample. The smaller the ΔL value, the better the scratch resistance of the material. The scratch resistance test results at room temperature (25°C) and after heat aging (102°C, 168h) are shown in Table 2.

[0075] The scratch resistance after thermal aging is characterized by the ΔL retention rate, and the calculation formula is: ΔL retention rate (%) = (ΔL t -ΔL 0 ) / ΔL 0 ×100%,ΔL t Indicates the scratch resistance test result after thermal aging, ΔL 0 Indicates the scratch resistance test results at room temperature;

[0076] (2) The tensile strength was tested according to ISO 527-2:2012. The specimen size was 170 mm × 10 mm × 4 mm and the tensile rate was 50 mm / min. The test results are shown in Table 2.

[0077] (3) Haze test: The haze of the polypropylene composition was tested using a 2 mm thick disc with a diameter of 80 mm according to TSM0503G ordinary B method. The lower the transmittance F (%) of all glass sheets, the higher the haze of the material and the higher the content of volatile small molecules. The test temperature was 100° C. The test results are shown in Table 2.

[0078] Table 3 Performance test results of Examples 1 to 15 and Comparative Examples 1 to 4

[0079]

[0080]

[0081] From the data of Examples 1 to 15, it can be seen that by adding acrylamide and POSS to the polypropylene system with amide substances as scratch resistant agents, the influence of amide scratch resistant agents on the haze of polypropylene materials and the influence of amide scratch resistant agents on the scratch resistance of materials due to their easy decomposition at high temperatures are overcome, and the prepared polypropylene composite material has both excellent scratch resistance at room temperature and high temperature and low haze, and surprisingly, the tensile performance is further improved. The light transmittance F value of the polypropylene composite material under the TSM0503G ordinary B method test conditions is above 80%, and can be as high as 88%; the scratch resistance can reach the level of ΔL<0.4, and the ΔL retention rate after heat aging is above 80%.

[0082] The results of Example 1 and Example 6 show that reducing the amount of added filler will reduce the tensile strength of the polypropylene composite material. At the same time, due to the increase in the content of the scratch-resistant agent in the polypropylene composite material, the scratch resistance of the material is improved and the haze is improved.

[0083] The results of embodiment 1 and embodiment 7-8 show that, within the dosage range provided by the present invention, as the dosage of acrylamide increases, scratch resistance and mechanical strength present a trend of first rising and then falling. The addition of acrylamide can act together with POSS to improve the light transmission performance of the composite material; but since acrylamide is a polar compound and polypropylene is a non-polar polymer, as in the polypropylene matrix, the amount of acrylamide continues to increase its content after increasing to a certain amount, and phase separation is very likely to occur in the polypropylene matrix, and polar acrylamide adsorbs more POSS, causing it to reunite particles in the polypropylene matrix, thereby causing the dispersibility of each component in the polypropylene matrix to deteriorate, thereby causing scratch resistance and mechanical strength to present a downward trend.

[0084] Examples 1 and 9-10 show that when the content of POSS increases to a certain amount, if it continues to increase, agglomeration will occur in the matrix, resulting in a decrease in mechanical properties. Within the above-mentioned dosage range of the present invention, the effect on the scratch resistance is small.

[0085] The results of Comparative Examples 1-3 show that acrylamide and POSS have a synergistic effect to improve the scratch resistance, tensile strength and transmittance F value of the polypropylene composite material.

[0086] The results of Comparative Example 4 show that when the amide scratch resistant agent is replaced by a non-amide scratch resistant agent, the room temperature and high temperature aging resistance scratch performance of the prepared polypropylene composite material becomes poor.

[0087] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A low haze scratch-resistant polypropylene composite material, characterized in that: By weight, it includes the following components: 100 parts of polypropylene, 0-55 parts of filler, 5-30 parts of acrylamide, 10-55 parts of POSS, 0.01-0.1 parts of amide anti-scratch agent, and 0-1 parts of other additives.

2. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the polypropylene at 230° C. and 2.16 kg is 1 to 60 g / 10 min.

3. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The polypropylene includes at least one of block copolymer polypropylene, homopolymer polypropylene and random copolymer polypropylene.

4. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the polypropylene at 230° C. and 2.16 kg is 10 to 35 g / 10 min.

5. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The filler includes at least one of talc, calcium carbonate, and basic magnesium sulfate whiskers.

6. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The POSS comprises at least one of octaaminopropyl cage-type polysilsesquioxane and its derivatives, octa-glycidyl cage-type polysilsesquioxane and its derivatives, octacarboxyethylene cage-type polysilsesquioxane and its derivatives, and octamethacryloxypropyl cage-type polysilsesquioxane and its derivatives.

7. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The amide anti-scratch agent includes at least one of erucamide and oleamide.

8. The low haze scratch-resistant polypropylene composite material according to claim 1, characterized in that: The other auxiliary agent is an antioxidant.

9. The method for preparing the low haze scratch-resistant polypropylene composite material according to any one of claims 1 to 8, characterized in that: The steps include: The raw material components are uniformly mixed and then melt-extruded to prepare the low-haze scratch-resistant polypropylene composite material.

10. Use of the low-haze scratch-resistant polypropylene composite material according to any one of claims 1 to 8 in the preparation of automobile parts.

Citation Information

Patent Citations

  • Crosslinking type polyhedral oligomeric silsesquioxane (POSS) / polypropylene (PP) composite diaphragm, and preparation method and application thereof

    CN110372962A

  • High-performance automotive modified polypropylene composite material based on functional POSS hybridization and preparation method thereof

    CN111087694A

  • High-scratch-resistance and light-transmitting polypropylene material as well as preparation method and application thereof

    CN117126493A

  • Compatilizer, polypropylene composite material and preparation method of polypropylene composite material

    CN117551236A

Cited By

  • Low-friction scratch-resistant master batch, polyester film and preparation method of low-friction scratch-resistant master batch

    CN120757990A